2004
DOI: 10.1046/j.1365-2796.2003.01289.x
|View full text |Cite
|
Sign up to set email alerts
|

Birth weight and cardiovascular risk factors in a cohort followed until 80 years of age: the study of men born in 1913

Abstract: Objectives. To analyse whether there is a relationship between birth weight and cardiovascular risk factors given the influence of potential modifying factors from birth time, former generations and adult life. Design. Population-based cohort followed until 80 years of age. Setting. Sweden. Subjects. A total of 478 singleton men born in 1913 and participating in a population study in Gothenburg, Sweden, from age 50. Main outcome measures. Systolic blood pressure (SBP), antihypertensive treatment, incident diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 55 publications
(75 reference statements)
2
41
0
Order By: Relevance
“…However, in macrosomic newborns of nondiabetic and nonobese mothers, serum lipid and apolipoprotein values did not differ significantly from those in AGA newborns (8,11). A population study in Uppsala, Sweden, of adult men showed a significantly positive correlation between birth weight and HDL cholesterol levels when adjusted for BMI (27). A study in 8-year-old Indian children also demonstrated a trend for rising HDL cholesterol concentrations with increasing birth weight, which was not, however, statistically significant (28).…”
Section: Results -The Mean (ϯSd) Anthropometric Indexes Of the 37mentioning
confidence: 87%
“…However, in macrosomic newborns of nondiabetic and nonobese mothers, serum lipid and apolipoprotein values did not differ significantly from those in AGA newborns (8,11). A population study in Uppsala, Sweden, of adult men showed a significantly positive correlation between birth weight and HDL cholesterol levels when adjusted for BMI (27). A study in 8-year-old Indian children also demonstrated a trend for rising HDL cholesterol concentrations with increasing birth weight, which was not, however, statistically significant (28).…”
Section: Results -The Mean (ϯSd) Anthropometric Indexes Of the 37mentioning
confidence: 87%
“…This led to hypothesis that maternal conditions in the prenatal period might have an important impact on the emergence of later vascular disease, and to the use of size at birth as a proxy for prenatal conditions (Barker, Osmond, Golding, Kuh, and Wadsworth, 1989). The relationship between size or relative thinness at birth and the risk of a group of chronic diseases including heart and vascular diseases, adult-onset diabetes, and the cluster of conditions known as the "metabolic syndrome" has since been observed in numerous different populations (Barker, 1995;Eriksson, Forsen, Tuomilehto, Osmond, and Barker, 2000;Eriksson, Wallander, Krakau, Wedel, and Svardsudd, 2004;IsmailBeigi, Catalano, and Hanson, 2006;Rich-Edwards et al, 1999;Rich-Edwards et al, 2005). The effect of birth size is not simply a confounded effect of postnatal conditions, but it does interact with them to influence chronic disease outcomes.…”
Section: Fetal Programming In Human Epidemiologymentioning
confidence: 99%
“…Caloric supplementation of pregnant women, as well as folic acid and iron supplements, reduced the incidence of low birth weight (22,28,30), whereas a diet rich in vegetables and fruits (important sources of folate, carotenoids, and antioxidants) was strongly associated with increased birth weight in rural India (122). Risk factors for cardiovascular disease, such as smoking, diet, a sedentary lifestyle, social status, and alcohol consumption, do not affect the relationship between low birth weight and cardiovascular disease (44,63,79,123). The most frequently studied association is between low birth weight (or IUGR) and hypertension (68,88).…”
Section: The Barker Hypothesismentioning
confidence: 99%